Effect of altitude on thrombopoietin and the platelet count in healthy volunteers - Hartmann, Sabine; Krafft, Alexander; Huch, Renate; Breymann, Christian (Thrombosis and Haemostasis, 2005)
Although there is evidence that altitude increases the platelet count, its effect on the platelet precursor stimulating factor, thrombopoietin (TPO), is unclear. Unlike erythropoietin, TPO appears largely unresponsive to exogenous signals. In a study in 16 healthy volunteers,we report the effects of altitude exposure at between 1000 and 1822 m for 1 or 2 weeks on TPO, the platelet count (+ indices), erythropoietin, hemoglobin, hematocrit and erythrocytes (+ indices).There were significant post-expo-sure increases in TPO (57.9 vs 37.1 U/l; P = 0.0006), platelet count (219.1 vs 208.0 x 103/ml; P = 0.031) and erythropoietin (16.1 vs 9.9 U/l; P = 0.0032).There was a positive correlation between the increases in TPO and platelet count (r = 0.52, P = 0.043). Hemoglobin and hematocrit remained unchanged. Our results provide clear evidence for a relationship, presumably driven by hypoxia, between altitude exposure,TPO production and the platelet count.
Keywords: Thrombopoietin; erythropoietin; hypoxia; altitude